Conserving goat sperm post-thawed gene expression and cellular characteristics using the antioxidant coenzyme Q10 supplementation - Oktanella, Yudit; Mustofa, Imam; An-Haru, Fahrunnisak Al-Firda Razak; Putri, Desinta Dwi Melati; Hendrawan, Viski Fitri; Susilowati, Suherni; Degu, Nurhusien Yimer; Hernawati, Tatik (Veterinary World, 2024)
Background and Aim: The use of frozen goat semen for artificial insemination frequently results in a decline in sperm quality following thawing, which can be attributed to cold shock from cryopreservation, reduced motility, and possible DNA damage. Freezing may compromise mRNA stability due to the presence of free radicals. Despite strong post-thaw motility and no visible DNA fragmentation, sperm can still exhibit altered gene expression patterns. To reduce the damaging impact of free radicals during cryopreservation, antioxidants are typically added to the freezing medium. This study assessed the impact of adding coenzyme Q10 (CoQ10) to frozen sperm diluent on the ATP5F1A and CPT2 gene expression, sperm motility, and viability post-thawing. Materials and Methods: CoQ10 was added to sperm at six different concentrations: 0 mg/dL (P0), 6.25 mg/dL (P1), 12.5 mg/dL (P2), 25 mg/dL (P3), 50 mg/dL (P4), and 100 mg/dL (P5). The Statistical Package for the Social Sciences (SPSS) software version 22 was used to conduct comparative tests using one-way analysis of variance followed by Duncan’s test for motility and viability and Kruskal–Wallis test followed by pairwise comparison test for membrane integrity and gene expression. Results: The addition of CoQ10 to semen diluent has a notable impact on the post-thawed quality of sperm. The most significant outcomes were observed with a 25 mg/dL dosage (P3) for cell viability, membrane integrity, and ATP5F1A gene expression, and with a 50 mg/dL dosage (P4) for sperm motility, membrane integrity, and CPT2 gene expression. Conclusion: Incorporating CoQ10 into frozen semen diluent improves gene expression and prevents deterioration of the cell quality of thawed goat spermatozoa. While the study demonstrates the benefits of CoQ10, the precise molecular mechanisms through which CoQ10 enhances gene expression and cell quality were not fully elucidated. Further investigation is needed to understand these mechanisms in detail. Comparative studies with other antioxidants and cryoprotectants can help establish the relative efficacy of CoQ10 and potentially develop more effective combinations.